Effect of Soaking Treatment on Anthocyanin, Flavonoid, Phenolic Content and Antioxidant Activities of Dioscorea alata Flour - Ratnaningsih Ratnaningsih; Nur Richana; Sakae Suzuki; Yoshiharu Fujii (Universitas Gadjah Mada, 2018)
Purple Dioscorea alata is one kind of tuber crops that rich in polyphenolic compounds. In Indonesia, the utilization of this yam is still very limited because it is easily damaged on the fresh form. Due to its high perishability, then the fresh tuber have to be processed into dried materials to expand its utilization. This study investigated the effect of browning inhibition treatments (immersion in water, Na-bisulfite, and ascorbic acid) on moisture, color, anthocyanin, flavonoid and phenolic content, and determined the antioxidant activities of D. alata flour. The moisture content of D. alata flour ranged between 6.89 to 7.71% db, which still in the range of wheat flour moisture content standards using Codex Standard. Browning inhibition treatment improved the color appearances and provided better values on anthocyanin, phenolic, and flavonoid content of D. alata flour. The color and antioxidant activities of D. alata flour were significantly correlated with its functional properties.